An Epidemiological Study of Snake Envenomation in a Tertiary Care Hospital of North India - Amit Kumar; Shweta Tanwar; Rajesh Chetiwal; Rajesh Patnaik Thonangi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Purpose: To study the epidemiological profile, clinical features, complications, and outcome of snake bite cases in a tertiary care teaching hospital in north India.Materials and Methods: A prospective cohort study of snake bites was carried out from June 2012 to October 2013. Data was collected regarding the socio-demographic profile, clinical features, complications, management and the outcome. The ICU LOS and the associated mortality were taken as the measures of outcome.Results: Out of the total 88, majority of the victims were rural men in the age group of 21-30 years. More than 90% of incidents were reported during the monsoon season. Neuroparalysis was present in 92% of patients. The mean bite to hospital time was 5.66 ± 1.78 hours. All patients had received polyvalent ASV with a mean dose of 20.85 ± 5.73 vials. 61.36% patients required ventilatory support with mean duration of 5.22 ± 7.69 days. The ICU LOS was observed to be 4.83 ± 6.96 days and associated mortality rate was 6.8%.Conclusion: There is urgent need to create awareness amongst the vulnerable population. To get a real picture of the burden, information need to be collected from community based surveys along with the peripheral primary healthcare centers